The Role of the Village Consultative Body in Oversight of the Village Revenue and Expenditure Budget Based on Law no. 6 of 2014 concerning Villages - Metry Widya Pangestika (Indonesian State Law Review, 2019)
This study aims to analyze the implementation of the role of Badan Permusyawaratan Desa (BPD) in monitoring the management of APBDes based on Law No. 6 of 2014 on Villages and the impact on APBDes Management by taking a case in Gemiringlor Village, Nalumsari District, Jepara District. The research method is sociological juridical. The results of this study indicate that the implementation of the role of BPD as a supervisor or controller of village administration performance in terms of preparing and managing APBDes in Gemiringlor Village, Nalumsari Subdistrict, Jepara Regency is not optimal due to limited Human Resources owned by the BPD deemed inadequate, the minimum salary received by the BPD from the Administration, the limited facilities and infrastructure as well as the lack of responsibility of the BPD for the main tasks and functions provided by Law No. 6 of 2014 concerning Villages. Law No. 6 of 2014 had an impact on the management of the APBDes by strengthening the politicization of the BPD to strengthen the control and legitimacy of the power of the village head and his apparatus. At the same time communication between the BPD and village Administration is carried out through village deliberations that can avoid head-to-head conflictual relations between the village's Chief and BPD. Indirectly, the relationship between the Village's Chief and BPD is a partnership to build a constructive cooperative relationship for the betterment of the village